Measuring the Unmeasurable: Upholding Rigor in Quantitative Studies of Personal and Social Development in Outdoor Adventure Education. (March 2015) - Scrutton, Roger; Beames, Simon
Outdoor adventure education (OAE) has a long history of being credited with the personal and social development (PSD) of its participants. PSD is notoriously difficult to measure quantitatively, yet stakeholders demand statistical evidence that given approaches to eliciting PSD are effective in their methods. Rightly or wrongly, many stakeholders want evidence in numbers and not anecdote. This article examines 22 recent studies and 6 meta-analyses in the peer-reviewed literature that have made use of quantitative methods to measure PSD in OAE. The investigation revealed three recurring problem areas that are effectively weakening the body of literature: the sample, the questionnaire and its use, and management of variables. Examples of good practice are reviewed and concrete suggestions made to uphold methodological rigor.